A review of installation, operation and maintenance of Internal Combustion Engine (ICE) powered lighting sets in a developing country - Olabiyi, B. A.; Adegbola, A.A.; Kolawole, P. (2012)
This review presents the important of constant power supply as a great measure of developed economy. Nation with epileptic power supply was considered as developing or under develop nation trying to prolong her development. The risk of losing potential investors is a possibility. Nigeria was used as a case study of a developing country facing an extreme electricity shortage for many years. This deficiency was discovered to be multi-faceted, with causes that are financial, structural, and socio-political, none of which are mutually exclusive. The purpose of this paper is to inform the concern authority of developing nations understand the risks of having poor power supply and understand the role of carbon dioxide and other emissions from internal combustion engine powered set installations. These power sets are very important and popular in Nigeria. Some designs met emergency power needs, with automatic start-up device to supply emergency power to all vital loads requiring uninterrupted power. The national line was found to be the stand-by power source while the use of diesel generators became the main source for micro power grids in remote areas for Agricultural needs. Barge-Mounted generators supply power to marine areas. Information Technology (IT) and data centres are at the mercy of generators. Infrastructure development in Nigeria generally depends on generators; the sets are the solution bridging the gap between power demand and supply. It is a revolutionary product that brings clean and affordable power within the reach of millions of enterprises, homes and small businesses in a developing economy. The installations, operation and maintenance of stand by generators are the main solutions to domestic power needs and also high-energy requirements in developing nations.